2000
DOI: 10.1002/1096-8628(20000619)92:5<318::aid-ajmg5>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Mosaic telomeric (2;14) association in a child with motor delay

Abstract: In a 6-year-old girl referred because of mild motor delay and hyperextensible joints, chromosome analysis disclosed a derivative chromosome consisting of end-to-end fusion of chromosomes 2 and 14. Two cell lines existed in which this telomere association was present, one with a 45,XX,tas(2;14)(q37;p11) karyotype and one with a 45,XX,tas(2;14) (q37;q32) karyotype. The cell line with the telomeric fusion of 2q and 14p was present in 90% of the cells; a telomeric fusion of 2q and 14q was seen in the remaining 10%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…TAs have been mostly reported in various leukemias and solid tumors (renal tumor, squamous cell carcinoma, cardiac myxoma, giant cell tumor of bone) and exceptionally in constitutional cells. To our knowledge, only seven patients from five different families carrying a constitutional TAs with TTAGGG telomeric sequences at the junction of the TAs have been previously published [Sawyer et al, ; Engelen et al, ; Zneimer et al, ; Huang et al, ; Josifova et al, ] (Table ). We did not include the rare cases for which the presence of telomeric sequences at the junction of the TA was not proven experimentally.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…TAs have been mostly reported in various leukemias and solid tumors (renal tumor, squamous cell carcinoma, cardiac myxoma, giant cell tumor of bone) and exceptionally in constitutional cells. To our knowledge, only seven patients from five different families carrying a constitutional TAs with TTAGGG telomeric sequences at the junction of the TAs have been previously published [Sawyer et al, ; Engelen et al, ; Zneimer et al, ; Huang et al, ; Josifova et al, ] (Table ). We did not include the rare cases for which the presence of telomeric sequences at the junction of the TA was not proven experimentally.…”
Section: Discussionmentioning
confidence: 99%
“…The patients were healthy with normal intelligence, except two of them. A 6‐year‐old girl presented with mild learning disability [Engelen et al, ] and a de novo tas(2;14) without loss of chromosomal material in the derivative chromosome. The authors concluded that the chromosome abnormality likely did not explain the learning disability of the patient.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have found 14 published cases involving chromosome 18; this chromosome appears to be most frequently involved in these structural rearrangements (Table II). As far as we know, only a few articles describe cases involving other chromosomes (chromosome 2 [Wyandt et al, 1982], chromosomes 2 and 14 [Engelen et al, 2000], chromosome 4 [Pescia et al, 1982; Smeets et al, 1998; Doco‐Fenzy et al, 1999; Schinzel, 2000; Syrrou et al, 2001], chromosome 5 [Perfumo et al, 2000], chromosome 8 [Van Balcom et al, 1992], chromosome 9 [Leung and Rudd, 1988], chromosome 11 [Pettenati et al, 1993; Tharapel et al, 1999], chromosome 13 [Fryns et al, 1979; Jalal et al, 1990; Duckett et al, 1992], chromosome 17 [Scriven and Docherty, 1992], and X chromosome [Pettenati et al, 1993]). The general “gene poverty” of chromosome 18 [International Human Genome Sequencing Consortium, 2001] could explain why this chromosome appears to be most frequently involved in structural rearrangement mosaicisms that are compatible with life.…”
Section: Discussionmentioning
confidence: 99%